WHY DOES TRANSMISSION LICENSEE SHOULD HAVE BULK SUPPLY TRANSACTION ACCOUNT IN VERTICALLY INTEGRATED UTILITY IN MONOPOLISTIC ELECTRICITY MARKET OF SRI LANKA - Jayawardena, J G L S; Kumara, U Anura; Sriyalatha, M A K (PEOPLE: International Journal of Social Sciences, 2019)
Sri Lanka has monopolistic electricity market dominated by Ceylon Electricity Board (CEB) in all three aspects of electricity i.e. Generation, transmission and distribution. The Public Utilities Commission of Sri Lanka (PUCSL) is the regulatory authority for the electricity sector. PUCSL has informed CEB for establishment of an effective and transparent mechanism to carry out Bulk Supply Transaction Account (BSTA) for implementation of a transparent Tariff Regime. However still CEB has not agreed to establish the BSTA. Since this is an issue where both parties are arguing advantages and disadvantages it was studied qualitatively to figure out the reasons and solution. Hence the objective of the study is to reason out the importance of BSTA and to identify the obstacles of establishing BSTA. We interviewed Director General PUCSL, Transmission Licensee and Distribution licensees of CEB, Lanka electricity Company officials, Donor Agencies and independent experts. It was revealed that the reasons highlighted by the advantages of having BSTA are improvement of efficiency, monitoring by the management on functions and sound financial situation of utility and the counter arguments made by Senior officials of CEB are at present CEB has separate accounting system for transactions, threat of unbundling, no legal provision to do it. However, under the existing legal framework there is no requirement to establish separate physical bank accounts for each licensee of CEB, considering the reasons explained by both parties it can be concluded that implementation of BSTA is important to improve the effective and transparent financial system in the CEB. But it is necessary to have clear legal provisions. However, BSTA is an integral part of tariff methodology. Hence it is necessary to have good tariff methodology for the sector to ensure the financial viability of the utilities.